DNA polymorphism in loci associated with the adaptation of barley to environmental conditions, when comparing seed samples from archaeological excavations of the 12th century with the VIR collection accessions of different geographical origin - T. V. Semilet; N. A. Shvachko; O. N. Kovaleva; L. Yu. Shipilina; E. K. Khlestkina (Биотехнология и селекция растений, 2024)
When studying the DNA polymorphism of ancient seeds from archaeological excavations, and comparing them with modern ones, it is possible, depending on the evolutionary significance/neutrality of the identified differences, to either find traces of adaptation of genotypes used in ancient times to unfavorable environmental conditions, or to clarify the origin of the samples, establishing additional evidence of trade and economic ties between different regions in different eras. The purpose of this work was to study the DNA polymorphism by comparing the 12th-century barley seeds from the Usvyaty settlement of the Pskov Region and VIR collection accessions of different geographical origin using the CHI and ELF3 gene fragments sequencing data. Of the 18 polymorphic SNP loci identified in the studied genes during the analysis of the barley samples under study, seven SNPs were from the regions amenable for resequencing in ancient DNA samples. The identified allelic changes in those seven SNP loci were neutral and did not lead to amino acid substitutions, therefore they can be used for a comparative analysis of the sample origin. The haplotype revealed in ancient barley based on the seven studied SNPs did not completely coincide with any of the studied accessions from the VIR collection. At the same time, rare alleles showed similarities with a Belarusian cultivar ‘Krinichny’, and the frequently occurring ones with several accessions of H. vulgare L. of different origin (Sweden, Denmark, Armenia), as well as with H. spontaneum (K. Koch) Thell.